5G555 time base circuit based on intelligent sensor in automotive electrical appliances. (7th October 2022) - Chen, Hejuan
With the development of the Internet of Things (IoT), more and more attention is paid to the design and integration of sensor circuits in intelligent vehicles. In this paper, the 5G555 time base circuit is used to combine the analogue circuit and logic circuit of the intelligent sensor processing module. Middle-Scale Integration (MSI) and Large-Scale Integration (LSI) are mainly used as circuit function modules. The combined circuit and sequential circuit are added to the function module to achieve the effect of intelligent sensor segment delay and a large amount of data processing. Research shows that, compared with the 5G1555 circuit, the static power consumption of the 5G555 time base circuit is reduced by 25%, and the range of power supply voltage is larger. The intelligent sensor of the 5G555 time base circuit can effectively improve the stability of automobile circuits, and improve the safety of automobile driving.